Association Between Maternal Occupation and History of Vaginal Discharge with Premature Rupture of Membranes: A Cross-Sectional Study - Nur Aldita Enisaputri; Irmayanti; Andi Elis; Andi Maryam (Fakultas Kedokteran, Universitas Papua, 2026)
Premature rupture of membranes (PROM) is an important obstetric complication that contributes to increased maternal and neonatal morbidity and mortality. Maternal factors, including occupation and a history of vaginal discharge, have been suggested to be associated with PROM; however, existing evidence remains inconsistent. This study aimed to examine the association between maternal occupation, a history of vaginal discharge, and the occurrence of PROM at Paniai Regional General Hospital. An analytical observational study with a cross-sectional design was conducted among 101 women who delivered in August 2024 using a total sampling technique. Data were collected from medical records using an observation checklist and analyzed using descriptive statistics and the Chi-square test with a significance level of 0.05. Most participants were aged 20–35 years (61.4%), had completed senior high school (55.4%), and were homemakers (64.4%). Overall, 77.2% experienced PROM, while 38.6% had a history of vaginal discharge. Significant associations were identified between maternal occupation and PROM (p = 0.007), as well as between a history of vaginal discharge and PROM (p < 0.001). Maternal occupation and a history of vaginal discharge may be considered during antenatal risk assessment to support the early identification and prevention of PROM.